Exploring Duolinggo and Babbel Mobile Applications in Improving EFL Slow Learners’ Speaking Performance: A Classroom Action Research - Baiq Zohratun Nafisah; M Wahyu Hadi; Muhammad Yani; Teresso Tafaa (Journal of Linguistic Metacognition and Language Learning, 2026)
This study explores the impact of Duolingo and Babbel, two widely used mobile applications, on improving the speaking performance of slow learners in English as a Foreign Language (EFL) contexts. The research adopted a qualitative approach within the framework of Classroom Action Research (CAR), targeting 35 slow EFL learners who were identified based on their previous academic performance and difficulties in speaking skills. The study aimed to assess the effectiveness of these mobile applications in enhancing learners' pronunciation, fluency, and vocabulary mastery. Data were collected through semi-structured interviews and classroom observations, providing both subjective insights and objective behavioral data. The findings indicated that both Duolingo and Babbel significantly improved learners’ pronunciation by offering consistent pronunciation practice and real-time feedback through speech recognition technology. The applications also contributed to improved fluency by providing repetitive language tasks, which helped reduce pauses and hesitation in speech. In terms of vocabulary mastery, the apps facilitated vocabulary acquisition through context-based exercises, enabling learners to expand their active vocabulary. However, the study also found that while these applications were effective in controlled tasks, learners still faced challenges in applying their skills during spontaneous conversations. The study concludes that Duolingo and Babbel are effective tools for supporting slow learners in language acquisition but highlights the need for a blended learning approach combining mobile apps with real-life communicative tasks for more substantial improvements in speaking skills.